Uji Efektifitas Antioksidan Minyak Zaitun terhadap Malondialdehyde (MDA) pada Tikus Hiperglikemia - Okvenda, Ariani Zaltin; Yerizel, Eti; Yerizel, Raveinal; Yerizel, Almurdi (Jurnal Biomedika dan Kesehatan, 2023)
Background Hyperglycemia is a medical condition that increases blood glucose levels beyond normal limits because the body lacks enough insulin or insulin does not work properly and is known to trigger oxidative stress. In cells sensitive to Hyperglycemia, such as endothelial cells, excessive glucose loads trigger the formation of Reactive Oxygen Species (ROS) in mitochondria, impairing mitochondrial function. ROS are essential mediators for activating pro-inflammatory signaling pathways; obesity and hyperglycemia-induced ROS production may support the induction of proinflammatory macrophages such as M1 during the onset and development of diabetes. Consumption of olive oil can increase plasma antioxidant capacity and reduce oxidative stress markers. Methods This study aimed to determine the effectiveness of olive oil antioxidants against Malondialdehyde (MDA) in hyperglycemic rats. This is an experimental design with a post-test-only group design. Adult male Wistar rats were divided into three groups (n = 8): negative control (K-), positive control (K+), and treatment (P). The normality test was conducted using the Shapiro-Wilk test, followed by Kruskal Wallis. Results The olive oil was proven to reduce levels of Malondialdehyde in the P group, with an average of 2.29 nmol/mL lower than the K+ group. Although the olive oil reduced the average MDA level in hyperglycemic rats, the post-hoc test showed no difference in MDA between the K+ and P groups (p-value = 0.226). Conclusions Antioxidants in olive oil may effectively lower blood glucose levels, reducing levels of Malondialdehyde in hyperglycemic rats.